KUALITAS PELAYANAN PUBLIK PELAKSANAAN PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL DI PUSKESMAS TILANGO KABUPATEN GORONTALO - Novi Dima Andayani; Fenti Prihatini Tui; Rustam Tohopi (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
This study aims to evaluate the quality of public services for BPJS (Social Security Organizing Agency) participants at the Puskesmas (Public Health Center) of Tilango, as assessed through five dimensions: (a) tangibles, (b) empathy, (c) reliability, (d) responsiveness, and (e) assurance. A qualititative apporoach was employed, specifically a descriptive qualitative reseacrh design, with data collection techniques including observation, interviews, and documentation. The findings og the study indicate tha the quality of public setvice for the BPJS (Social Security Organizing Agency) program at the Puskesmas Tilango, assessed through the five dimensions of : (a) tangibles, (b) empathy, (c) reliability, (d) responsiveness, and (e) assurance, is generally satisfactory and meets the needs of the service users the community. However, some indicators do not fully meet public expectations. For example, in terms of tangibles. There is a lack of seting in the waiting area, leading some patients to sit on the floor and a deficiency in air conditioning.